2023
DOI: 10.3389/fimmu.2023.1094611
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics of cardiac involvement in immune-mediated necrotizing myopathy

Abstract: ObjectiveTo investigate the characteristics of cardiac involvement due to Immune-mediated Necrotizing Myopathy (IMNM).MethodsPatients diagnosed with Immune-mediated Necrotizing Myopathy (IMNM) who attended the Department of Neurology and the Department of Rheumatology and Immunology at the First Medical Center of the PLA General Hospital between February 2011 and June 2022 were collected. Clinicopathological diagnosis of IMNM was performed according to the criteria established by the European Neuromuscular Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…20 These results are consistent with previous findings that rates of ILD, dysphagia, cardiac involvement, and severe weakness increase with disease severity. 19,21,22 Despite the impact of current macrophage markers on cardiac involvement is unclear, with persistent inflammation or cytokine storms as a plausible explanation. 23 Tissue-resident macrophages trigger two distinct responses through different metabolic programs: the destruction of infected tissue (inflammatory response, M1 macrophages) or the repair of damaged tissue (regenerative response, M2 macrophages).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…20 These results are consistent with previous findings that rates of ILD, dysphagia, cardiac involvement, and severe weakness increase with disease severity. 19,21,22 Despite the impact of current macrophage markers on cardiac involvement is unclear, with persistent inflammation or cytokine storms as a plausible explanation. 23 Tissue-resident macrophages trigger two distinct responses through different metabolic programs: the destruction of infected tissue (inflammatory response, M1 macrophages) or the repair of damaged tissue (regenerative response, M2 macrophages).…”
Section: Discussionmentioning
confidence: 99%
“…This process contributes to the development of a more severe clinical phenotype 13,18 . Cardiac involvement is a frequent complication of IMNM 19 . Autopsy findings reveal massive macrophage infiltration in both skeletal and cardiac muscle 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Suzuki et al identified cardiac involvement in only two of 100 patients with anti-SRP antibody-positive NAM [ 8 ]. A recent study in 2023 found that the prevalence of cardiac involvement in anti-SRP antibody myopathy was 50% (16/32) and included seven patients with acute coronary syndrome [ 9 ]. Takeguchi-Kikuchi et al demonstrated an association between anti-SRP antibody-positive NAM and cardiomyopathy, as proven by positive myocardial biopsy, cardiac MRI, and fluorodeoxyglucose-positron emission tomography [ 10 ].…”
Section: Discussionmentioning
confidence: 99%